2014
DOI: 10.1371/journal.pone.0097811
|View full text |Cite
|
Sign up to set email alerts
|

Active Invasion of Oral and Aortic Tissues by Porphyromonas gingivalis in Mice Causally Links Periodontitis and Atherosclerosis

Abstract: Atherosclerotic vascular disease is a leading cause of myocardial infarction and cerebrovascular accident, and independent associations with periodontal disease (PD) are reported. PD is caused by polymicrobial infections and aggressive immune responses. Genomic DNA of Porphyromonas gingivalis, the best-studied bacterial pathogen associated with severe PD, is detected within atherosclerotic plaque. We examined causal relationships between chronic P. gingivalis oral infection, PD, and atherosclerosis in hyperlip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
215
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 156 publications
(227 citation statements)
references
References 38 publications
3
215
2
3
Order By: Relevance
“…ApoE -/-male mice (strain B6.129P2-Apoe tm1Unc/J , N = 12) were sham-infected or monoinfected for 12 weeks via the oral route, with the P. gingivalis FDC 381 strain (5×10 9 bacteria / mL), as described previously [35]. …”
Section: P Gingivalis Infection Mouse Modelmentioning
confidence: 99%
“…ApoE -/-male mice (strain B6.129P2-Apoe tm1Unc/J , N = 12) were sham-infected or monoinfected for 12 weeks via the oral route, with the P. gingivalis FDC 381 strain (5×10 9 bacteria / mL), as described previously [35]. …”
Section: P Gingivalis Infection Mouse Modelmentioning
confidence: 99%
“…This primary environmental risk factor (infection) has the potential for pathogenic interplay in the hetero/homozygous apoε4 genotype via initiation of an intrinsic cascade of risk factors (infection>inflammation) for dyslipidaemia. Another common feature of all the mono and polyinfected experiments in ApoE −/− mice [71,75] was the abundant expression of NPY gene in vascular tissues [75]. This suggests an intricate relationship of NPY gene and chronic infections with possible manifestation for the development of insulin resistance as discussed below.…”
Section: Periodontal Disease In Apoe −/− Micementioning
confidence: 89%
“…These studies have demonstrated bacterial colonization and progression of PD in the ApoE −/− mouse model (bacterial invasion, gingival inflammation, apical migration of junctional epithelium, alveolar bone resorption, and intra-bony defects). By comparing control to infected mice, a significantly elevated IgG response to P. gingivalis and T. denticola and T forsythia mono-infections as well as in the polymicrobial infections was recorded [70][71][72]. The 8 humoral response generated in all of the infected groups, provides further evidence of a stable response to PD pathogens as well as manifestation of chronic inflammation [70][71][72].…”
Section: Periodontal Disease In Apoe −/− Micementioning
confidence: 90%
See 2 more Smart Citations